2008
DOI: 10.1111/j.1365-2486.2008.01597.x
|View full text |Cite
|
Sign up to set email alerts
|

Warming and elevated CO2 affect the relationship between seed mass, germinability and seedling growth in Austrodanthonia caespitosa, a dominant Australian grass

Abstract: While the influence of elevated CO 2 on the production, mass and quality of plant seeds has been well studied, the effect of warming on these characters is largely unknown; and there is practically no information on possible interactions between warming and elevated CO 2 , despite the importance of these characters in population maintenance and recovery. Here, we present the impacts of elevated CO 2 and warming, both in isolation and combination, on seed production, mass, quality, germination success and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
80
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 36 publications
4
80
1
1
Order By: Relevance
“…However, in contrast with what occurred with total seedling biomass, this effect was not related to differences in seed provisioning. In accordance with previous studies (Hovenden et al, 2008), when considering the whole data set, we found that SM was negatively correlated with seedling RSR, with the smaller seeds leading to seedlings with greater RSR. However, when considering the effect of the maternal environment, we found that the stressful environment strongly determined a lower seedling RSR, even when the SM in that environment was the smaller.…”
Section: Maternal Environmental Effects On Sm Variabilitysupporting
confidence: 78%
See 4 more Smart Citations
“…However, in contrast with what occurred with total seedling biomass, this effect was not related to differences in seed provisioning. In accordance with previous studies (Hovenden et al, 2008), when considering the whole data set, we found that SM was negatively correlated with seedling RSR, with the smaller seeds leading to seedlings with greater RSR. However, when considering the effect of the maternal environment, we found that the stressful environment strongly determined a lower seedling RSR, even when the SM in that environment was the smaller.…”
Section: Maternal Environmental Effects On Sm Variabilitysupporting
confidence: 78%
“…Those SM-dependent epigenetic mechanisms, that is, a mixture of heritable and non-heritable maternal effects (sensu Boyko and Kovalchuk, 2011), are feasible whenever epigenetic regulation is resource dependent. Other authors have also found a significant SM Â maternal environment interaction on seedling growth, but they did not study the responsible mechanisms (Hovenden et al, 2008). Nevertheless, irrespective of the involved mechanisms, our results suggest that the maternal environment, rather than directly affecting the seedling total dry mass, modulates the extent to which the seedling phenotype depends on the SM, that is, a regulatory maternal effect.…”
Section: Maternal Environmental Effects On Sm Variabilitymentioning
confidence: 36%
See 3 more Smart Citations